Spontaneous base flipping helps drive Nsp15’s preferences in double stranded RNA substrates - Zoe M. Wright; Kevin John Butay; Juno M. Krahn; Isha M. Wilson; Scott A. Gabel; Eugene F. DeRose; Israa S. Hissein; Jason G. Williams; Mario J. Borgnia; Meredith N. Frazier; Geoffrey A. Mueller; Robin E. Stanley (Nature Communications)
Abstract Coronaviruses evade detection by the host immune system with the help of the endoribonuclease Nsp15, which regulates levels of viral double stranded RNA by cleaving 3′ of uridine (U). While prior structural data shows that to cleave double stranded RNA, Nsp15’s target U must be flipped out of the helix, it is not yet understood whether Nsp15 initiates flipping or captures spontaneously flipped bases. We address this gap by designing fluorinated double stranded RNA substrates that allow us to directly relate a U’s sequence context to both its tendency to spontaneously flip and its susceptibility to cleavage by Nsp15. Through a combination of nuclease assays, 19F NMR spectroscopy, mass spectrometry, and single particle cryo-EM, we determine that Nsp15 acts most efficiently on unpaired Us, particularly those that are already flipped. Across sequence contexts, we find Nsp15’s cleavage efficiency to be directly related to that U’s tendency to spontaneously flip. Overall, our findings unify previous characterizations of Nsp15’s cleavage preferences, and suggest that activity of Nsp15 during infection is partially driven by bulged or otherwise relatively accessible Us that appear at strategic positions in the viral RNA.